New mixed ligand copper(II) hydrazone‐based complexes: Synthesis, characterization, crystal structure, DNA/RNA/BSA binding, in vitro anticancer, apoptotic activity, and cell cycle analysis. (19th October 2021) - Elsayed, Shadia A.; Elnabky, Islam M.; di Biase, Armando; El‐Hendawy, Ahmed M.
Abstract: Four new mixed ligand copper(II) complexes with the general formula [Cu(L)(B)]n (1 )–(4 ) (H2 L = dehydroacetic acid benzoyl hydrazone Schiff base, B = H2 O (1 ), DMSO (2 ), imidazole (imz) (3 ), n  = 1) or pyridine (py) (4 ), n  = 2) were synthesized. Characterization was performed by elemental analyses, FTIR, 1 H NMR, electron paramagnetic resonance (EPR), ESI‐mass, and UV–visible) spectroscopy, together with magnetic susceptibility and molar conductivity measurements. The molecular structure of (2 ) and (4 ) complexes was investigated by X‐ray crystallography. The ligand behaves as a di‐basic tridentate ONO donor, coordinating to copper(II) center via deprotonated hydroxyl group, azomethine nitrogen, and deprotonated amide oxygen in a square planar (1 )–(3 ) /square pyramidal geometry (4 ). The intercalation binding mode of the compounds with calf thymus DNA (ct DNA) and yeast (tRNA) and strong static interaction with bovine serum albumin (BSA) protein have been evaluated by absorption and emission spectroscopy. Further, in vitro cytotoxic activity of the compounds was examined on three human cancer cell lines; breast cancer (MCF7), colon cancer (HCT116), liver cancer (HepG2), and a normal lung fibroblast cell line (WI38) using cisplatin as a standard. Based on IC50 and therapeutic indices (TI), complexes (3 ) and (4 ) showed better activity than that of cisplatin. So both complexes were subjected for further studies viz, DNA fragmentation, cell apoptosis (annexin), and cell cycle analysis. They induced DNA fragmentation, and the HCT116 and HePG2 cell death were induced using (3 ) and (4 ) complexes, respectively, by apoptosis and cell cycle arrest at the G2/M phase. Abstract : Four new mixed ligand copper(II) complexes of dehydroacetic acid benzoylhydrazone have been prepared and characterized. Interactions with ct DNA, tRNA (intercalative), and BSA (static) have been studied absorption and emission spectroscopy. In vitro cytotoxicity, DNA fragmentation, cell apoptosis, and cell cycle analysis have activities have also evaluated.